METTL14 modulates the nasopharyngeal carcinoma microenvironment via m6A-modified YWHAH identified through single-cell and machine learning analyses - Liang, Zuming; Zhou, Zhihao; Wang, Jing; Shen, Lingjun; Li, Yiran; Zhu, Litong; Hong, Gengrui; Li, Qiwen; Xiao, Dong; Lin, Xiaolin; Lin, Taoyan (Frontiers in Immunology, 2026)
BackgroundNasopharyngeal carcinoma (NPC) is an aggressive malignancy with endemic prevalence in southern China. Emerging evidence highlights the critical function of the N6-methyladenosine (m6A) methylation in NPC progression, where sustained cytokine activity contributes to immunosuppression and immune evasion.MethodsSingle-cell RNA sequencing (scRNA-seq) and bulk RNA sequencing datasets were obtained from the GEO database. High-dimensional downstream analyses, including hdWGCNA, cell–cell communication, and pseudotime analysis was performed to characterize cellular interactions and transcriptional programs. Machine learning algorithms and immune infiltration profiling were integrated with MeRIP-seq to identify the key m6A-regulated gene. The post-transcriptional regulatory role was further validated in NPC cells with overexpression or knockdown of METTL14, or in cells with YWHAH silenced.ResultsB cells were identified as the primary senders to the TNF pathway, with epithelial and myeloid cells acting as influencers and receivers. YWHAH emerged as a key TNF-associated, m6A-regulated gene, with elevated expression in naive/GC B cells, interleukin (IL)-1β+ tumor-associated macrophages, and differentiated epithelial cells. METTL14-deficient increased YWHAH transcript abundance and RNA stability, whereas TNF-α stimulation further enhanced YWHAH expression. Conversely, YWHAH knockdown impaired NPC cell migration and upregulated IL−6/IL−8 expression, effects that were partially rescued by TNF−α treatment.ConclusionIntegration of multi-omics data facilitated the identification of YWHAH as a METTL14-regulated gene, which plays a pivotal role in the NPC immune microenvironment. The elevated expression of YWHAH indicates its role in regulating immune balance. Together these findings suggest a potential regulatory link between TNF-α, YWHAH and METTL14 in the context of NPC.